Publication crimes in Bahraini press Law (Decree No. (47) of 2002: A comparative study with the laws of the GCC (The International Journal for Scientific Research, 2025)
The study aims to examine publication crimes under Bahraini press law and compare them with the laws of the Gulf Cooperation Council (GCC) member states, focusing on the similarities and differences. It seeks to understand the criminal liability within Bahraini press law, analyze these legal frameworks, and identify legislative gaps that can contribute to amending the law's provisions.A descriptive-analytical and comparative methodology was employed to analyze legal texts and compare the similarities and differences between press laws in Bahrain and relevant GCC states concerning publication crimes and criminal liability.The findings concluded that there are legislative gaps in Bahraini press law that have not been addressed by the legislator. The current law restricts press freedom, does not serve the public interest, and is inconsistent with international best practices.The study recommends the repeal or amendment of provisions criminalizing publication to align with freedom of opinion and expression. It advocates for the abolition of imprisonment penalties for journalists, which constitute a severe infringement on journalistic freedom, and emphasizes the need for a new press law that meets the desired aspirations.
Keywords: Bahraini Press Law; Publication Crimes; Journalists' Criminal Liability